Impact of leverage ratios on earnings per share (EPS) of Indian cement manufacturing companies - Rengasamy, Dhanuskodi (-, 2014)
The leverage ratio occupies a key role in the earnings per share (EPS). Leverage causes variability in the returns of shareholders (Pandey, 2008). The objective of the study is to determine the impact of leverage ratios on earnings per share of Indian cement manufacturing companies listed in the Bombay stock exchange. The leverage ratios have been measured through debt ratio, long term debt to equity ratio and debt to equity ratio and are the independent variables of the study. EPS determine the company’s stock value in the market, and also determine the path of company’s future earnings and it is treated as a dependent variable for the study. The present research work is based on historical accounting data. The study was adopted the expost facto research design. The study covers a period of four years from 2009 to 2012. The data interpretation was made by ratios, mean, standard deviation and correlation. The study applied annual reports of 25 selected companies. The study concluded that the leverage ratios of selected companies have no significant relationship with EPS. Further, three leverage ratios have negative impact on EPS during the study period.